Critical Success Factors of Electronic Payment Services: Interpretive Structural Modeling (ISM) - Hunitie, Mohammad Faleh Ahmmad (Migration Letters, 2023)
The aim of this study is to explore critical success factors (CSFs) of using electronic payment systems (EPS) and building a research conceptual framework using theoretical and empirical insights. Following the Interpretive structural modeling (ISM) methodology. Eighteen CSFs of EPS were elucidated based on a review of the literature, 10 were used as a baseline for the study. A panel of experts consisting of 10 academics and managers were asked to assess these CSFs. ISM was conducted using SmartISM (http://smartism.sgetm.com). The results showed that 7 factors were identified as CSFs of using EPS and the proposed model of the CSFs of EPS should incorporate customer technological capacity and government regulations as independent variables, system perceived usefulness as a dependent variable, and customer personal information, customer perceived security, system reliability, and system perceived risks as mediating variables. Results, conclusion, theoretical and empirical implications as well as recommendations are provided.